Reshaping Spaces and Relations: Urban Gardening in a Time of Crisis - Cangelosi, Elisabetta (PARTECIPAZIONE E CONFLITTO, 2015)
This article studies urban gardening as a form of social resilience. It analyses its role and impact on society in a context of social and financial crisis through the lens of the debate about the commons on the basis of three case studies conducted in Brussels in 2013. The study connects the specificities of the current social and economic context with the new wave of urban gardening from a people-centred perspective. Both the motivations and the outcomes of this form of activism are analysed and led to the conclusion that being involved in urban gardening represents not only a way to cope with economic and social threats but also a tool to rebuild and reshape social bonds. The paper aims to contribute to the current debate about the commons, intended as a form of resilience and a tool of social change rather than a simple alternative economic model. It aims to do so through the analysis of urban gardening practices, which are more commonly studied from the perspective of urban agriculture, food production, access to land and urbanism.